(untitled) (Mustansiria Dental Journal, 2018)
Dental trauma is a public health problem in young aged patients. The aim of this study was to investigate the percentage and severity of dental trauma and malocclusion and their correlation, as well as analyze the general risk factors like the effect of age, gender, causes of the trauma and malocclusion in anterior permanent teeth. The sample of the present study include patients who came to the Pedodontic clinic in the Pedodontic and Preventive department at the College of Dentistry/Baghdad University seeking treatment of traumatized anterior permanent teeth. The traumatized teeth were examined clinically (according to Garcia-Gody classification) and radiographically. Types of occlusion was determined according to Angle’s classification, while the over jet and overbite were recorded according to the coding criteria described by Kinnan’s study. In all age groups, the most frequent cause of trauma was found to be falls (61.4%). Enamel and dentin fracture was the most frequently seen type of injury(38.6%) in which upper central incisors were the most affected teeth from dental trauma(47.7%).Regarding malocclusion, patients with class II malocclusion represent (71.9%) from the total sample, while those with increased over jet (26.3%) in which (66.7) of them seek treatment for two fractured teeth. However, the number of injured teeth per child was 1.54. Increased overbite was correlated with more sever type of dental trauma. There is a relationship between malocclusion and fractured anterior teeth in which malocclusion will increase the number of fractured teeth as well as the severity of dental trauma